The Influence of Investment Interest on Investment Decision Making: Penelitian - Burhanuddin Jauhari; Whilis Aziz Panji Pamungkas; Yopy Ratna Dewanti; Gusneli; Akbar Tanjung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This is a quantitative study with an explanatory approach, an approach that relies on all fundamental research sources from previous, similar studies. The data used in this study is primary data obtained by the researcher from 235 economics students at several universities in Indonesia. The data obtained was analyzed using the smart PLS 4.0 analysis tool. The conclusion in this article show that the Investment Interest variable has a positive relationship direction and a significant influence on Investment Decisions because the P-Values ​​are trending towards positive and are below the 0.05 significance level, namely 0.003. These results mean that Investment Interest can help employees improve Investment Literacy which leads to Investment Decisions. Investment Decisions can improve employees' financial conditions, stabilize them, and make it easier for students to achieve their goals. Based on this, it can be concluded that the first hypothesis in this article can be accepted and proven.